Shifting Meanings of Art: A Narrative Analysis of Coloring Competitions as a Social Practice in Early Childhood - Andreas Teguh Nurcahyanto; Suharti Suharti; Yes Matheos Lasarus Malaikosa; Rachma Hasibuan (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2026)
This study aims to understand the experiences of children, parents, and teachers in early childhood education coloring competitions, as well as the meanings constructed within these practices. The study used a qualitative approach based on narrative inquiry. Data were analyzed using reflexive thematic analysis to identify patterns of meaning across participants’ narratives. Data were collected through participant observation, semi-structured interviews, and documentation conducted during a coloring competition event held in Surabaya. The participants consisted of six children aged 4-6 years, five parents, and three teachers or organizers selected through purposive sampling. Data analysis followed Braun and Clarke’s six phases: familiarization, coding, theme generation, theme review, theme definition and naming, and report writing. The findings indicate that parents’ motivations range from recreational to competitive orientations. Teachers and organizers tend to maintain coloring competitions for practical reasons, while children’s responses range from enthusiasm to pressure. These findings suggest that coloring competitions serve as a social practice that shapes children’s experiences within a competitive value framework. This study offers a critical perspective on art practices in early childhood education. In practice, it suggests reorienting art activities toward more appreciative formats, such as open-ended drawing festivals that allow children to express themselves without competitive pressure.